Analisis Konflik Sudan dan Sudan Selatan Pasca Referendum Pemisahan Diri Sudan Selatan dari Sudan - Cahyanti, Putri; Utomo, Tri Cahyo; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Conflict is a circumstance which conflict actors such as individuals or groups have dispute between each other to gain the same goal(s). Conflict actors may use violent or peaceful means to settle the conflict. One way to end it is to use referendum of secession if conflict happens within a state territory. South Sudan did referendum of secession in 2011 due to prolonged conflict with Sudan since 1955. But in fact, after South Sudan's independence, conflicts have continued between Sudan and South Sudan such as oil conflicts and border conflicts. This research’s aim is to know why Sudan and South Sudan still in conflict even after South Sudan did referendum of secession in 2011. This research use The Conflict Triangle theory and Conflict Dynamcis theory and is qualitative type that intend to understand social phenomenon. The research results are Sudan and South Sudan still in conflict even after South Sudan’s secession because both parties has not reach agreement in South Sudan’s oil transit price that will be exported through Port Sudan, both parties are accused in funding the rebel forces in each territory, and there is no agreement yet regarding border area especially Abyei. Author suggest Sudan and South Sudan should immediately discuss their conflict over border area so that conflict source can be resolved properly and dialogue between both parties should be necessary so there will be no misunderstandings abouth funding the rebel forces in each territory.